Deskripsi Perilaku Pemilih Etnis Banjar Pada Pilkada Gubernur dan Wakil Gubernur serentak Kalimantan Tengah 2020 - Ricky Zulfauzan; Charles Hutapea; Nur Elysa Mitharie (Society, 2022)
This study was motivated by the low voter turnout in the 2020 Regional Head Election for Governor and Vice Governor in Central Kalimantan Province, Indonesia. The Banjar ethnicity was chosen because the Banjar ethnicity is the third largest ethnic majority in Central Kalimantan, so the behavior of the Banjar ethnicity can determine political contestation in Central Kalimantan. This study aimed to find out and analyze the behavior of the Banjar Ethnic voters. Qualitative research methods with a descriptive approach. The focus of the research is the behavior of ethnic Banjar voters, with research benchmarks using the Voter Behavior theory as follows: (a) Rational Voters, (b) Critical Voters, (c) Skeptical Voters (d) Traditional Voters. The results of the study, after the informants were interviewed, it was found that the behavior of ethnic Banjar voters mostly claimed to be rational voters, but the characteristics shown were closer to traditional voters. The critical behavior of ethnic Banjar towards prospective candidates did not combine a high orientation towards the performance of political parties and skeptical behavior towards ethnic behavior. Their Banjar is not oriented towards ideology or party and candidate policies. The behavior of traditional voters in Ethnic Banjar can be classified as traditional voters because issuing voting rights prioritizes socio-cultural closeness, origin, ethnicity and religion. This study concludes that the Banjar Ethnic voters’ behavior belongs to the Traditional Voters.